(untitled) (Bangladesh Journal of Medical Microbiology, 2023)
Clinical outcomes of chronic hepatitis C virus (HCV) infection include liver cirrhosis, liver failure, and hepatocellular carcinoma (HCC). Acute infection is usually asymptomatic, and chronic hepatitis is common. Hepatic involvement is crucial leading to liver cirrhosis and carcinoma. Pathogenesis of HCC is not yet completely understood. We tried here to discuss the structure of HCV, immune-pathogenesis, development of cirrhosis and carcinoma in diminutive and unpretentious arrangement. Bangladesh Journal of Medical Microbiology, January 2023;17(1):1-2